Distribution of putative denitrifying methane oxidizing bacteria in sediment of a freshwater lake, Lake Biwa - Kojima, Hisaya; Tsutsumi, Masazumi; Ishikawa, Kanako; Iwata, Tomoya; Mußmann, Marc; Fukui, Manabu (Systematic and applied microbiology, 2012)
Methane oxidation coupled to denitrification is mediated by ‘Candidatus Methylomirabilis oxyfera’, which belongs to the candidate phylum NC10. The distribution of putative denitrifying methane-oxidizing bacteria related to “M. oxyfera” was investigated in a freshwater lake, Lake Biwa, Japan. In the surface layer of the sediment from a profundal site, a phylotype closely related to “M. oxyfera” was most frequently detected among NC10 bacteria in PCR analysis of the 16S rRNA gene. In the sediment, sequences related to “M. oxyfera” were also detected in a pmoA gene library. The presence of NC10 bacteria was also confirmed by catalyzed reporter deposition fluorescence in situ hybridization (CARD-FISH). Denaturing gradient gel electrophoresis (DGGE) and quantitative real-time PCR indicated that the abundance of the “M. oxyfera”-related phylotype was higher in the upper layers of the profundal sediment. The horizontal distribution of the putative methanotrophs in lake sediment was also analyzed by DGGE, which revealed that their occurrence was restricted to deep water areas. These results agreed with those in a previous study of another freshwater lake, and suggested that the upper layer of the profundal sediments is the main habitat for denitrifying methanotrophs.